RESPON TANAMAN KEDELAI (Glycine max (L), Merril) TERHADAP PEMBERIAN KAPUR DOLOMIT DAN PUPUK MIKROBA M-Bio PADA TANAH GAMBUT PEDALAMAN - Arief Rahman; Suparno Suparno; Shella A.J. W. (Agrienvi: Jurnal Ilmu Pertanian, 2021)
This research was conducted on farmers' land in Pulau Damar village, Banjang district, Hulu Sungai Utara Regency from February to May 2019. The study was aimed to determine the effect of dolomite lime and M-bio microbes on soybean yield in peat soil. Experiments were arranged based on a factorial randomized block design with three replications. The first factor is dolomite lime which consists of 3 levels, namely was 0, 3, and 6 t ha-1, and the second factor is M-bio microbe fertilizer which consists of 4 levels, namely 0, 2, 4, and 6 ml L 1 water. The results showed that the interaction between dolomite lime and M-bio microbe fertilizer significantly affected the dry weight of 100 soybean seeds but did not significantly affect the number of filled pods per plant, the number of seeds per plant, and the chlorophyll content of soybean leaves. The highest dry weight of 100 grains of 10.08 g plant-1 was obtained by giving 3 t ha-1 dolomite lime and 6 ml L-1 water of M-bio microbe fertilizer.